A novel tool for evaluating children's musical abilities across age and culture - Peretz, Isabelle; Gosselin, Nathalie; Nan, Yun; Caron-Caplette, Emilie; Trehub, Sandra E.; Béland, Renée (Frontiers in Systems Neuroscience, 2013)
The present study introduces a novel tool for assessing musical abilities in children: The Montreal Battery of Evaluation of Musical Abilities (MBEMA). The battery comprises tests of memory, scale, contour, interval, and rhythm, is administered to 245 children in Montreal and 91 in Beijing (Experiment 1), and an abbreviated version is administered to an additional 85 children in Montreal (in less than 20 min.; Experiment 2). All children are 6 to 8 years of age. Their performance indicates that both versions of the MBEMA are sensitive to individual differences and to musical training. The sensitivity of the tests extends to Mandarin-speaking children despite the fact that they show enhanced performance relative to French-speaking children. Because this Chinese advantage is not limited to musical pitch but extends to rhythm and memory, it is unlikely that it results from early exposure to a tonal language. In both cultures and versions of the tests, amount of musical practice predicts performance. Thus, the MBEMA can serve as an objective, short and up-to-date test of musical abilities in a variety of situations, from the identification of children with musical difficulties to the assessment of the effects of musical training in typically developing children of different cultures.